Fertilizante foliar em associação com fungicida em trigo - Marques, Leandro Nascimento (2014)
The Chemical control of diseases is the most used practice in wheat. The increase in mineral nutrition with foliar fertilizers has been a promising alternative for the plant resistance against leaf diseases. However, foliar fertilizers have been applied in association with fungicides and can change the performance of the fungicide on diseases control. This study aimed to evaluate the applicability of foliar fertilizer in combination with azoxystrobin + cyproconazole fungicide in wheat, based on biochemical, physiological , nutritional and yield parameters and determine the interference caused by the fertilizer on the evolution of leaf diseases in wheat. Isolated application rates of fertilizer and application in combination with the fungicide were performed on field and in the greenhouse works. The application of fertilizer increased the plant growth, green leaves and enhanced pigments levels (Chl a, Chl b and carotenoids). When the fungicide was applied with fertilizer, it reduced the stresses effect generated by fungicide application; it increased parameters of chlorophyll fluorescence, Fv / Fm and ETR. The levels of N, P and K in the leaves increased after fertilizer application. The fertilizer mixed with fungicide did not reduce the fungicide uptake. The diseases control was better when fertilizer was mixed with fungicide. The fertilizer applied alone had no effect on the diseases. Yield parameters were increased due to application of fungicide and foliar fertilizer.